1989
DOI: 10.1002/ep.3300080217
|View full text |Cite
|
Sign up to set email alerts
|

Field evaluation of nitric oxide abatement with ferrous chelates

Abstract: The absorption of nitric oxide fromflue gas streams presents some unique problems due to its low solubility in conventional scrubbing solutions. A process is being developed that utilizes an electrolytic cell to reduce Fe(ZZZ) to Fe(ZZ) and maintain the mujority of the iron chelate in the active ferrous state. This process has been tested on an actual flue gas stream and achieved 80% nitric oxide abatement. Further reduction of nitric oxide is possible with increased stages.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

1990
1990
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(22 citation statements)
references
References 2 publications
0
22
0
Order By: Relevance
“…The reaction of Fe II (L) with NO was studied by pulse-irradiation of aqueous solutions containing 2 m Fe III (L), 58Ϫ170 µ NO, 1  methanol, and either 2 m acetate or phosphate buffer. Under these conditions, e Ϫ aq reduces Fe III (L) to Fe II (L) and · OH is scavenged by CH 3 OH to produce · CH 2 OH as shown in Equations (4) to (6). (The numbers in parenthesis are G values, which represent the number of molecules formed per 100 eV energy absorbed by pure water.…”
Section: Employed Kinetic Techniquesmentioning
confidence: 99%
“…The reaction of Fe II (L) with NO was studied by pulse-irradiation of aqueous solutions containing 2 m Fe III (L), 58Ϫ170 µ NO, 1  methanol, and either 2 m acetate or phosphate buffer. Under these conditions, e Ϫ aq reduces Fe III (L) to Fe II (L) and · OH is scavenged by CH 3 OH to produce · CH 2 OH as shown in Equations (4) to (6). (The numbers in parenthesis are G values, which represent the number of molecules formed per 100 eV energy absorbed by pure water.…”
Section: Employed Kinetic Techniquesmentioning
confidence: 99%
“…Some recent pilot studies with metal chelates (particularly iron EDTA) have indicated NO, removals of 70% to 90%, utilizing techniques such as an electrolytic cell to maintain reactivity or high temperature regeneration [3]. Comparable simultaneous SO2 removal can be achieved.…”
Section: Flue Gas Denitrification (Fgdn)mentioning
confidence: 96%
“…[1][2][3][4][5][6][7][8][9] After the complex processes have been studied for more than 20 years, it is clear that it is difficult for the absorption solution to be regenerated and reused circularly, and the commercial applications of the process have been impeded because of the following problems. First, ferrous ion can be oxidized easily to ferric ion by the oxygen (O 2 ) in the flue gases, and the ferric chelates cannot complex with NO; therefore, the amount of removal NO in the process decreases rapidly.…”
Section: Introductionmentioning
confidence: 99%